2012
DOI: 10.1097/npt.0b013e3182462ea6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Altered Corticomotor System Connectivity in Early-Stage Alzheimer's Disease

Abstract: Background and Purpose There is increasing evidence for subtle motor dysfunction early in Alzheimer’s Disease (AD), including common motor behaviors that were once considered unaffected early in the disease process. Our objective was to assess if functional neural networks underlying motor behavior are altered by AD. Methods We investigated AD-related differences in regional brain activation during motor performance. Nine older adults with early-stage AD and 10 without dementia underwent fMRI while performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 54 publications
(60 reference statements)
3
31
0
2
Order By: Relevance
“…Patients with MCI have demonstrated similar hippocampal deactivation to those with AD during recall [59], but with hyperactivation during encoding phases [60, 61], which might underline mechanistic compensation in prodromal stages. fMRI findings in AD extend to tasks of working memory, visuospatial ability, attention, semantic knowledge, and motor performance [6266] and in MCI tasks of attention and working memory [62, 64, 67]. …”
Section: Functional Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MCI have demonstrated similar hippocampal deactivation to those with AD during recall [59], but with hyperactivation during encoding phases [60, 61], which might underline mechanistic compensation in prodromal stages. fMRI findings in AD extend to tasks of working memory, visuospatial ability, attention, semantic knowledge, and motor performance [6266] and in MCI tasks of attention and working memory [62, 64, 67]. …”
Section: Functional Imagingmentioning
confidence: 99%
“…Increased activation was found for MCI patients relative to control subjectsYetkin et al [62]Task-based fMRI11 AD, 10 MCI, 9 controlsIncreased activation in frontal and temporal regions, fusiform gyrus, and anterior cingulate gyrus was displayed for AD and MCI patients during a working memory task. For selected areas, MCI patients showed greater activation than AD patientsThiyagesh et al [63]Task-based fMRI12 AD, 13 elderly control subjectsDeclines in activation in parietal, parieto-occipital, and premotor cortical areas and increased activation of additional parietal structures was found in AD during an observational visuospatial taskLi et al [64]Task-based fMRI10 AD, 9 MCI, 9 elderly control subjectsReduced activation was found in prefrontal cortical areas for AD patients and increased activation in these same regions was found for MCI patients during a Stoop colour–word interference taskMcGeown et al [65]Task-based fMRI29 AD, 19 controlsNo activation in parietal regions and decreased activation in prefrontal areas was found for AD patients during a semantic knowledge taskVidoni et al [66]Task-based fMRI9 AD, 10 controlsReduced activation was found in the premotor and supplementary motor regions, and the cerebellum, whilst increased activation was evidenced in the primary motor cortices for AD patients during a motor taskVan Dam et al [67]Task-based fMRI8 aMCI, 8 controlsIncreased activation was shown in the tempero-parietal junction, angular gyrus, and precuneus, whereas attenuated activation was seen in prefrontal regions and the anterior cingulate for aMCI patients during an attentional (executive control, alerting and orienting) taskGreicius et al [69]Resting-State fMRI15 AD, 18 controlsReduced connectivity was shown between medial temporal structures and the posterior cingulate cortex for AD patientsDamoiseaux et al [71]Resting-State fMRIBaseline: 21 AD, 18 controlsFollow-up: 11 AD, 10 controlsCompared to control subjects at baseline, declines in connectivity were seen in the posterior DMN and increased activation was found for areas within the ventral and anterior DMN for AD patients. Compared to control subjects at follow-up, decreased connectivity between regions within the anterior, ventral, and posterior DMN in addition to sensorimotor network were shown for AD patients.…”
Section: Functional Imagingmentioning
confidence: 99%
“…Other groups observed that the glucose metabolism in the cerebellum was significantly lower in patients with AD comparing to healthy controls and this reduction correlated with MMSE [87]. Using functional MRI (fMRI), Vidoni and colleagues [88] observed that individuals without dementia exhibited greater activation in accessory motor regions supplementary motor area and cerebellum compared to those with AD.…”
Section: Section 6: Radiological Biomarkers Of Cerebellar Alteration mentioning
confidence: 99%
“…[10][11][12] Degradation of gait and balance was formerly thought to be a late sequelae of AD, but more recent evidence demonstrates these activity limitations early in the course of the disease. [13][14][15][16] Balance exercise programs have been shown to be effective in improving balance 17 and reducing falls 18 in older adults without cognitive defi cits but have not been well studied in IwAD.…”
Section: Introductionmentioning
confidence: 99%